(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The study area along the northeast border of Iraq is a perfect location to test the notion of an index to predict relative tectonic activity, as well as being considered a very characteristic area as include three main tectonic zones (High Folded Zone, Imbricate Zone and Zagros Suture Zone). This study area has variable rates of active tectonics resulting from the collision of Arabian and Iranian plates. This study aims at highlighting the possibility of information systems programs in building a morphometric geographic database of the Rawanduz River Basin, which is one of the main basins of the Greater Zab River using Shuttle Radar Topographic Mission (SRTM), Digital Elevation Model (DEM 90 m) data to evaluate the drainage condition of this river with the help of Geographical Information Systems (GIS) and Remote Sensing. The morphometric analysis of the Rawanduz drainage basin has been executed during measurement of linear, areal and relief aspects as well as we offer a new process for estimate relative active tectonics according on geomorphic indices useful in evaluating morphology and topography. A total of 26 sub-basins were delineated in the Rawanduz River Basin. Geomorphic indices used include: drainage basin asymmetry (Af), ratio of valley-floor width to valley height (Vf), index of drainage basin shape (Bs), and index of mountain front sinuosity (Smf). Results from the analysis are accumulated and expressed as an index of relative active tectonics (Iat), which we divide into four classes from relatively low to higher tectonic activity.